Natural dynamics and watershed approach incorporation in urban water management: A scoping review. - Marcelo Canteiro; Helena Cotler; Marisa Mazari-Hiriart; Nadjeli Babinet; Manuel Maass (PLoS ONE)
Several cities are facing water emergencies related to urbanization impact and amplified by climate change. Most of the cities have responded to these crises through short-term measures. However, some cities have incorporated a watershed approach to water management in seeking more sustainable solutions. Although the importance of a watershed approach in land management is generally acknowledged, studies on this topic have typically focused on theoretical models, water management in rural areas or single case-studies of cities or countries. In this research, a scoping review of the literature was performed, based on the PRISMA 2020 statement, in three databases: Web of Science, Google Scholar and SciELO. Forty-one studies were identified analyzing 17 city cases implementing urban actions from a watershed approach in water management. These cities were from the Global North and Asian rising world powers. The lack of results of cities from the Global South, based on the research undertaken, was the main limitation and bias identified. Most of the Global South results identified in this research were theoretical models, scenarios and cases of rural areas instead of urban contexts. The results obtained indicate that the main motivations for cities to implement a watershed approach were water scarcity, floods and contamination of water bodies. The implemented actions focused on the shift from gray to green and blue infrastructure and on conservation measures. Lastly, the challenges to introduce those actions were mainly the lack of economic investment, insufficient experience, stakeholder opposition, and regulatory obstacles. Urban water management could be seen as an opportunity to change the way we relate to urban territory. Incorporating a watershed approach into urban planning and water management could promote more sustainable cities.